Effect of Sperm Concentration and Storage Temperature on Goat Spermatozoa during Liquid Storage - Sara Sadeghi; Raquel Del Gallego; Balma García-Colomer; Ernesto A. Gómez; Jesús L. Yániz; Jaime Gosálvez; Carmen López-Fernández; Miguel A. Silvestre (Biology, 2020)
The use of cooled semen is relatively common in goats. There are a number of advantages of cooled semen doses, including easier handling of artificial insemination (AI) doses, transport, more AI doses per ejaculate, and higher fertility rates in comparison with frozen AI doses. However, cooled semen has a short shelf life. The objective of this study was to examine the effect of temperature and sperm concentration on the in vitro sperm quality during liquid storage for 48 h, including sperm motility and kinetics, response to oxidation, mitochondrial membrane potential (MMP) and DNA fragmentation in goats. Three experiments were performed. In the first, the effects of liquid preservation of semen at different temperatures (5 °C or 17 °C), durations (0, 24 and 48 h) and sperm concentrations (250 × 106 sperm/mL (1:2 dilution rate), 166.7 × 106 sperm/mL (1:3 dilution rate) or 50 × 106 sperm/mL (1:10 dilution rate)) on sperm motility and kinetics were studied. In the second experiment, the effect of temperature, sperm washing and concentration on sperm motility and DNA fragmentation was studied. Finally, the effect of sperm concentration and duration of storage at 5 °C on sperm motility, response to oxidative stress and MMP was examined. We found that refrigerated liquid storage of goat sperm impaired sperm quality, such as motility, MMP and response to oxidation, as storage time increased; however, sperm DNA fragmentation index was not significantly affected. Liquid storage at 5 °C preserved higher total motility than at 17 °C. Moreover, we observed that the reduction of sperm concentration below 500 × 106 sperm/mL did not seem to improve the quality of spermatozoa conserved in milk-based extender in the conditions tested.